Pengaruh Operasi Patuh Dalam Usaha Mencegah Terjadinya Kecelakaan Lalu Lintas Kajian (Pasal 360 (1) Kitab Undang-Undang Hukum Pidana - romlan prasodjo (Justicia Journal, 2015)
The problem posed is how to exercise held adherent operation carried out by the National Police in order to prevent the occurrence of traffic accidents, especially in cases of serious injuries (Pasal 360 (1) of the Criminal Law Act shrimp) in the region of Madiun District Police? and the purpose of this study is to further explore the effects of the operation on Patuh in efforts to prevent traffic accidents, especially in cases of serious injuries (Pasal 360 Penal Code). The research approach menggukanan literature 1. (library research) 2. The field research (field research) in Madiun region police office, and POLRES POLRESTA Madiun Madiun. Analysis of study data using the theory of deductive and inductive theory.The result showed that the implementation of Operation Patuh conducted by INP is an activity the use of force Police (POLRI) efforts mitigation efforts before the accident to prevent and counteract disturbances and threats in order to ensure security, order and smooth traffic on the highway on a public road.